1985
DOI: 10.1073/pnas.82.18.6114
|View full text |Cite
|
Sign up to set email alerts
|

Identification of intracellular degradation intermediates of aldolase B by antiserum to the denatured enzyme.

Abstract: A method has been developed that enables us to identify intracellular degradation intermediates of fructosebisphosphate aldolase B (D-fructose-1,6-bisphosphate D-glyceraldehyde-3-phosphate-lyase, EC 4.1.2.13). This method is based on the use of antibody against thoroughly denatured purified aldolase. This antibody has been shown to recognize only denatured molecules, and it did not interact with "native" enzyme. Supernatants (24,000 x g for 30 min) of liver and kidney homogenates were incubated with antiserum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…The protein content was higher in frozen cells (Fig. 7) and this could be due to protein fragments or peptides heavier than 3kDa, because intracellular protein degradation requires a sequential series of proteolytic events that result in the conversion of the native protein into free amino acids, but this process is preceded by production of intermediate, partially-proteolysed forms (Reznick et al, 1985). To confirm further the hypothesis of a degradation of proteins in frozen cells, we used SDS-PAGE (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The protein content was higher in frozen cells (Fig. 7) and this could be due to protein fragments or peptides heavier than 3kDa, because intracellular protein degradation requires a sequential series of proteolytic events that result in the conversion of the native protein into free amino acids, but this process is preceded by production of intermediate, partially-proteolysed forms (Reznick et al, 1985). To confirm further the hypothesis of a degradation of proteins in frozen cells, we used SDS-PAGE (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Antinative SOD antiserum reacted with either native or dena tured enzyme [see ref. 17 for theoretical explana tion].…”
Section: Methodsmentioning
confidence: 99%
“…The antiserum was used in immunoprécipitation studies as previously described [7,16,17], The amount of antigen per unit of enzyme activity was determined by overnight incubation at 4 "C of 1 unit of SOD with increasing amounts of monospe cific rabbit antihuman SOD IgG. After preincuba tion the samples were centrifuged at 5,000 g for 30 min and the supernatant assayed for residual SOD activity.…”
Section: Methodsmentioning
confidence: 99%
“…Reznick et al 13 ) identified degradation intermediates of aldolase B in mouse liver and kidney cells using antiserum against the denatured enzyme. This antiserum recognizes only inactive molecules and truncated polypeptides of aldolase B. Toda and Ohashi l4 ) purified degradation products of pig liver phosphofrutokinase by immunoaffinity chromatography.…”
Section: Discussionmentioning
confidence: 99%